Biochemical characterization of recombinant mevalonate kinase from Bacopa monniera - Kumari, Uma; Vishwakarma, Rishi K.; Sonawane, Prashant; Shakeel Abbassi; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2015)
Mevalonate kinase (MK; ATP: mevalonate 5-phosphotransferase; EC 2.7.1.36) plays a key role in isoprenoid biosynthetic pathway in plants. MK catalyzes the phosphorylation of mevalonate to form mevalonate-5-phosphate. The recombinant BmMK was cloned and over-expressed in E. coli BL21 (DE3), and purified to homogeneity by affinity chromatography followed by gel filtration. Optimum pH and temperature for forward reaction was found to be 7.0 and 30 degrees C, respectively. The enzyme was most stable at pH 8 at 25 degrees C with deactivation rate constant (Kd*) 1.398 x 10(-4) and half life (t(1/2)) 49 h. pH activity profile of BmMK indicates the involvement of carboxylate ion, histidine, lysine, arginine or aspartic acid at the active site of enzyme. Activity of recombinant BmMK was confirmed by phosphorylation of RS-mevalonate in the presence of Mg2+, having K-m and V-max 331.9 mu M and 719.1 pKat mu g(-1), respectively. The values of k(cat) and k(cat)/K-m for RS-mevalonate were determined to be 143.82 s(-1) and 0.43332 M-1 s(-1) and k(cat) and k(cat)/K-m values for ATP were found 150.9 s(-1) and 1.023 M-1 s(-1). The metal ion studies suggested that BmMK is a metal dependent enzyme and highly active in the presence of MgCl2. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Bacopa monniera; Enzyme kinetics; Mevalonate kinase; stability